The diagnostic advantage of immature platelet fraction and platelet indices in thrombocytopenia cases: Tertiary care center study - Rachana Pachkawade,; Girija,; Yaranal PJ,; Pratima Manohar Pattar, (Asian Journal of Medical Sciences, 2025)
Background: Thrombocytopenia, characterized by low platelet counts, is a common hematological disorder with diverse causes, complicating diagnosis. Distinguishing between central and peripheral causes is crucial for appropriate management. Automated hematology analyzers measuring platelet indices, especially immature platelet fraction (IPF), provide valuable insights, aiding early diagnosis, preventing unnecessary transfusions, and improving patient care. Aims and Objectives: To evaluate the role of platelet indices, particularly the IPF, in differentiating hyper-destructive from hypo-productive thrombocytopenia and its clinical relevance in patient management. Materials and Methods: This hospital-based case-control study was conducted in the Department of Pathology, SNMC, Bagalkote, over 6 months (April–September 2024), with 100 participants (50 cases and 50 controls). Blood samples were analyzed using the Mindray BC-6800 to assess platelet indices, including IPF. Data were analyzed using IBM SPSS 24. Results: The IPF reference range in healthy controls was 0.5–5.1%. Patients with peripheral platelet destruction had a significantly higher mean IPF of 16.24%, while those with decreased production had a mean IPF of 5.95%. Statistically significant differences (P<0.05) were observed between hyper-destructive, hypo-productive groups, and controls. Conclusion: IPF is a valuable, non-invasive, and cost-effective tool for assessing thrombocytopenia, offering a reliable alternative to bone marrow aspiration in distinguishing between central and peripheral causes.